From research to practice: building bridges to enhance interprofessional communication between general practitioners and acupuncturists. (2nd July 2020) - Roberts, Kate; Dowell, Anthony; Nie, Jing-Bao
ABSTRACT: Background: General practitioners (GPs) play an important role in integrated care management and in most cases act as the primary provider and access point for further services. In recent years more and more patients are using complementary and alternative medicine (CAM), including acupuncture, for the management of many health conditions. However, the interaction and collaboration between these two groups in relation to shared health care has not been investigated. Method: The project utilized a mixed methods multiphase design. A nationwide survey of 400 GPs and 250 acupuncturists was conducted. Univariate data was analysed using descriptive statistics. This was followed by individual semi-structured interviews of 13 purposively sampled acupuncturists, and 14 GPs which was analysed using thematic analysis. The project continued to data driven toolkit development and piloting to further address research's aims. Results: The research found that communication was not optimal between the participant groups and identified both facilitators and barriers to integrative care. Key barriers identified were: the lack of suitable pathways and methods for communication to occur, lack of awareness surrounding acupuncturists' scopes of practice, and the difficulties in identification of suitable practitioners. Conclusions: This research demonstrated that it is possible to create a toolkit containing elements which are readily included in routine clinical practice for both GPs and acupuncturists. These tools have clinical utility not only to enhance communication and collaboration between GPs and acupuncturists, but to allow transferability to other groups within health care.